Production and characterization of a monoclonal antibody against epirubicin - Papadopoulos, N. G.; Gritzapis, A. D.; Dedoussis, G. V.; Spanakos, G.; Baxevanis, C. N.; Papamichail, M. (Hybridoma, 1995)
Epirubicin is an anthracyclinic antibiotic that has been increasingly used in the treatment of a variety of malignancies. A hybridoma producing monoclonal antibody (MAb) against the drug was obtained by cell fusion. The MAb is of the IgM isotype and has an affinity constant of 1.4 x 10(-7) M. Inhibition analysis showed that the antibody recognizes an epitope related to the C 4'-hydroxyl group in the amino sugar moiety, distinguishing epirubicin from the closely related doxorubicin. Since the precise mechanism of anthracycline action as well as its immunomodulating effects are still under scrutiny, powerful tools for their study are clearly needed. Moreover, this MAb can be useful in monitoring the levels of epirubicin in treated patients, as well as for the construction of bispecific antibodies in tumor-targeting immunotherapy.
Keywords: Animals Antibodies; Bovine; Inbred BALB C Serum Albumin; Monoclonal Antibody Specificity Epirubicin Female Hybridomas Immunoconjugates Mice Mice